Managing the politics of innovation and sustainability. Issue 1 (19th May 2014) - Schepers, Stefan
<x xml:space="preserve">Abstract</x> Purpose Policy objectives and government interventions about sustainability resulting from social debates forces business models to adapt and determines the kind of innovation that is required and the ways in which it can be achieved. Yet, governments' role in defining sustainability and innovation is often overlooked, and new ways of managing the government dimension of sustainability is required as well as the development of corporate strategies encompassing inclusive visions of the corporations' role in society. Design/methodology/approach This article aims to examine the issue from various perspectives in view of doing further research. Findings The management of innovation for sustainability requires increased collaboration and mentoring by public governance systems and the elaboration of coherent and inclusive strategic visions also serving the public interest when setting corporate strategies. Originality/value The article is based on political and economic writings and on practical experience in the public and private sectors. Copyright © 2014 John Wiley & Sons, Ltd.